LEARNING MOTIVATION: ANALYSIS THE INFLUENCE OF FAMILY AND PEER ENVIRONMENT ON ONLINE BUSINESS AND MARKETING STUDENTS - Rahayu, Dian; Faslah, Roni; Fidhyallah, Nadya Fadillah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to examine the influence of family environment and peer environment on the learning motivation of students majoring in Online Business and Marketing (BDP) at SMKN 44 Jakarta. This study uses a quantitative approach. The population consists of all students majoring in Online Business and Marketing (BDP) in the 2023/2024 academic year totaling 174. From this population, a sample of 121 students was taken randomly using the probability proportional random sampling technique. The analysis in this study used SPSS 25 which includes classical assumption analysis, multiple regression, and coefficient of determination. The findings show a positive and significant influence between family environment and learning motivation, a positive and significant influence between peer environment and learning motivation, and a positive and significant influence between family environment, peer environment, and motivation to learn simultaneously.